Idiomer på nettet: Den danske idiomordbog og fraseografien. Center for Leksikografi, Aarhus Handelshøjskole, 2003. - Farø, Ken (HERMES - Journal of Language and Communication in Business, 2004)
The ﬁrst Danish electronic dictionary on idioms, Den Danske Idiomordbog, has been published by the Centre for Lexicography at the Aarhus School of Business, accessible directly via the Internet. This article, apart from reviewing the dictionary and its functions in general, aims at drawing a systematic picture of some of the methodological problems related to the discipline phraseography, taking the new dictionary as a starting point. Three significant issues should be mentioned here: The importance of a well reﬂected positive and operational idiom deﬁnition cannot be stressed too strongly, as it inﬂuences every choice made during the editing. Another difﬁculty which needs to be given more attention is the formal representation of the idioms, which could be carried out more adequately if thorough empirical evidence and linguistic tests were exploited systematically. And ﬁnally there is a need for a much stronger focusing on pragmatic constraints on idioms on the level of language use. Danish phraseology still needs to be discovered as an object of systematic scientiﬁc research as the discussed problems in Den Danske Idiomordbog are not at all singular but rather symptomatic for the genre phraseography as a whole.